Prosedur dan Pencapaian Kompetensi untuk Dancer pada Komunitas Baby Badazz Kota Malang - Tharisa Oktanita; Robby Hidajat (Universitas Negeri Medan, 2026)
This study examines the development of modern dance in Indonesia, particularly hip-hop, which attracts young people to explore their creativity through communities like Baby Badazz in Malang City. The purpose of this study is to describe the procedures and competency achievements of dancers in the Baby Badazz Community in Malang City. The method used is a qualitative approach with descriptive methods, involving participatory observation, in-depth interviews, and documentation at the research location. The results show that the training procedures include skill development stages (warm-up, basic movements, dance material), demonstration and drill methods, and evaluation through videos. Competency achievements are reflected in movement skills that include movement techniques, body coordination, and expression, which encourage personal growth and community sustainability. This study provides guidance for other communities to improve the quality of female dancers in hip-hop dance.